Literature Review: Intervensi Kebidanan Terkini Peningkatan Sikap Orang Tua dalam Memberikan Pendidikan Seksual Pada Anak untuk Pencegahan Child Sexual Abuse - Hafshah, Hafshah; Wardani, Diadjeng Setya; Gumanti, Kentri Anggarina (-)
Child sexual abuse cases reported in Indonesia are still high. Sexual issues are still taboo in society, parents in Indonesia don't care about sexual education for their child. Sexual education is important given to straighten understanding and positive sexual behavior of children. Providing appropriate sexual education can equip children to protect themselves from sexual abuse. Parents need to support and facilities to provide sexual education for their children. This study aimed to critically review literature, articles, and related documents research in measuring the effectiveness of health promotion interventions to improve parents' attitudes in providing sexual education for children as an effort in preventing child sexual abuse. In this study, researchers use the literature review method. Data were obtained from reputable journal articles published in the 2010-2020 period. To analysis the research, researchers use the PICO-T RCAC method (Population, Intervention, Compare / Intervention, Outcome, Time). Ten articles analyzed show that the interventions provided varied greatly in terms of content, methods, media, and duration. Interventions are training, counseling, psychoeducation, and educational drama that can improve parents’ knowledge, attitudes, and communication practices in preventing child sexual abuse and increasing parental awareness of the phenomenon of sexual harassment around their children. This study concludes that some health promotion interventions have been effective in improving parents' attitudes to be more positive in providing sexual education to their children.